Évaluation des activités antioxydante, anti-inflammatoire et antimicrobienne des extraits de delphinium. - AZZI , Lamia; SALAH, Souad; THAIBAOUI , Djihane Samah; NOUIOUA , Wafa (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine., 2023)
Medicinal and aromatic plants have been used in traditional medicine since antiquity as a source of seasoning or as a remedy. The objective of this study is to determine the content of total phenolic compounds and flavonoids of two extracts (aqueous and hydro-ethanolic) of the aerial part of Oriental Delphinium, and to test their antioxidant, anti-inflammatory and antimicrobial properties. The polyphenol content was determined by the Folin-Ciocalteu method and the flavonoid content was determined by the aluminum trichloride method. Antioxidant activity was assessed by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical test. The extracts showed a content of total phenolic compounds of 3.39 ± 0.176 and 3.586 ± 0.22 µg EAG/mg extract for the aqueous and hydro-ethanolic extract, respectively. A flavonoid content of 7.826 ± 0.208 and 9.812 ± 0.303 µg EQ /mg of extract, respectively. And a value of CI50: 128.22 ± 0.07 and 188 ± 13.97 µg/ml comparable to the effect of BHT with CI50: 6.29 ± 1.12 µg/ml for the DPPH test of the two aqueous and hydro-ethanolic extracts, respectively. For the anti-inflammatory test, the results showed that at low concentrations the antiinflammatory activity is average compared to diclofenac. The antimicrobial activity was evaluated for 04 bacterial strains (Gram-: Eschericha Coli ATCC 25922, Pseudomonas Aeruginosa ATCC 27853, and Gram+: Staphylococcus Aureus ATCC 25923, Bacillus Subtilis ATCC 6633), by the then diffusion method. The result was very low, almost nil for the two aqueous and hydro-ethanolic extracts.
استخدمت النباتات الطبیة والعطریة في الطب التقلیدي منذ العصور القدیمة كمصدر للتوابل أو كعلاج. الھدف من ھذه الدراسة ھو تحدید المحتوى الكلي للمركبات الفینولیة والفلافونوید من مستخلصین )مائي وإیثانول مائي( من الجزء الجوي من الدلفینیوم الشرقي ، واختبار خصائصھا المضادة للأكسدة والمضادة للالتھابات والمضادة للمیكروبات. تم تحدید محتوى وتم تحدید محتوى الفلافونوید بطریقة ثلاثي كلورید الألومنیوم. تم تقییم Folin-Ciocalteuالبولیفینول بواسطة طریقة أظھرت ).-diphenyl-1-picrylhydrazyl (DPPHنشاط مضادات الأكسدة عن طریق اختبار الجذور الحرة 2،2 للمستخلص EAG / mgالمستخلصات محتوى إجمالي المركبات الفینولیة 0.176 ± 3.39و 0.22 ± 3.586میكروغرام / EQالمائي والإیثانولي المائي على التوالي. محتوى الفلافونوید 0.208 ± 7.826و 0.303 ± 9.812میكروغرام من و 13.97 ± 188میكروغرام / مل مقارنة بتأثیر CI50: 128.22 ± 0.07من المستخلص ، على التوالي. وقیمة mg للمستخلصین المائي والإیثانولي المائي على التوالي. DPPHمیكروغرام / مل لاختبار CI50: 6.29 ± 1.12مع BHT بالنسبة للاختبار ً المضاد للالتھابات ، أوضحت النتائج أنھ عند التراكیز المنخفضة یكون النشاط المضاد للالتھاب متوسطا Gram- : Eschericha Coliمقارنة بالدیكلوفیناك ، وقد تم تقییم نشاط (مضادات المیكروبات لـ 04سلالات بكتیریة ATCC 25922, Pseudomonas Aeruginosa ATCC 27853, et Gram+ : Staphylococcus Aureus ATCC 25923, Bacillus Subtilis ATCC 6633 ) حیث كانت النتائج ضعیفة جدا تقریبا منعدمة بالنسبة للمستخلصین المائي و الایدروایثانولي
Keywords: activité anti-inflammatoire; activité antimicrobienne.activité antioxydante; Delphinium orientale; dosage des polyphénols; extrait aqueux; extrait hydro-éthanolique; flavonoïdes